PENGARUH SENSORY BRAND EXPERIENCE DAN PERCEIVED VALUE TERHADAP BRAND LOYALTY DENGAN BRAND TRUST SEBAGAI VARIABEL MEDIASI (PADA PERUSAHAAN SUBSCRIPTION VIDEO-ON-DEMAND (SVoD) NETFLIX) - Maulana, M. Rizky; Kusumawardhani, Amie (Diponegoro Journal of Management, 2024)
ABSTRACT This research aims to determine the influence of Sensory Brand Experience and Perceived Value on Brand Loyalty with Brand Trust as a mediating variable (at the Netflix Video-OnDemand (SVoD) Subscription Company). This research involved 200 Netflix user respondents in the Jakarta area, where the sampling was determined based on a purposive sampling technique. The instrument used in this research was a questionnaire with a Semantic Differential scale. Data analysis in this research is divided into two analyses, namely descriptive statistics and inferential statistics. In inferential statistics, data is processed using AMOS software version 25. The research results show that: (1) Sensory Brand Experience has a direct, positive and significant effect on Brand Trust, (2) Perceived Value has a direct, positive and significant effect on Brand Trust. (3) Sensory Brand Experience has a direct, positive and significant effect on brand loyalty. (4) Perceived value does not have a significant direct influence on brand loyalty. (5) Brand trust has a direct, positive and significant effect on brand loyalty. (6) Sensory brand experience has a significant effect on brand loyalty through brand trust. (7) Perceived value has a significant effect on brand loyalty through brand trust.